Huge Trichilemmal Carcinoma With Metastasis Presenting With Two Distinct Histological Morphologies: A Case Report - Xie, Yao; Wang, Lin; Wang, Tingting (Frontiers in Oncology, 2021)
Background Trichilemmal carcinoma (TC) is a rare malignancy of cutaneous adnexal carcinomas, with only 136 cases reported in the literature to date. It usually has an indolent course and benign clinical evolution, and only four cases with regional and distant metastasis have been reported. The tumor cells present with the characteristics of trichilemmal differentiation both in histology and immunohistology. Case presentation We report a case of TC on the scalp with an aggressive course that with metastases to the ipsilateral neck. Moreover, the lesions presented with two distinct histologic morphologies. Conclusion Despite an indolent course and benign clinical evolution, TC has the potential for local invasion and recurrence, which implies that early, correct diagnosis and careful follow-up are very important for patients. More than one specimen should be taken for histopathological examinations when the lesion is very large and characterized by different morphologies in the clinic.